A taxonomic revision of the Oriental species of Thaumatodryinus Perkins, with descriptions of two new species from P. R. China (Hymenoptera: Dryinidae) - Xu, Zaifu; Olmi, Massimo; He, Junhua (Zootaxa, 2009)
The Oriental species of Thaumatodryinus Perkins are revised. Two new species, Thaumatodryinus zhejiangensis and hainanensis, are described from the People’s Republic of China, respectively from Zhejiang Province, Qingliangfeng, and Hainan Province, Jianfengling. A new key to the Oriental Thaumatodryinus is presented.